Financial market supervision : some conceptual issues - Marquardt, Jeffrey C. (Basle : Bank for International Settlements, 1987)
This book discuss the conceptual issue involved in understanding the goal ,constraint and methodology of financial market.
Includes bibliographical references: p. 39-41.
oo 16/04/2019
Loans
Keywords: Monetary policy; Switzerland